Cloning and functional characterization of LCR-F1: a bZIP transcription factor that activates erythroid-specific, human globin gene expression. - Caterina, J J (1994)
DNase I hypersensitive site 2 (HS 2) of the human beta-globin Locus Control Region (LCR) directs high level expression of the beta-globin gene located 50 kilobases downstream. Experiments in cultured cells and in transgenic mice demonstrate that duplicated AP1-like sites in HS 2 are required for this powerful enhancer activity. A cDNA clone encoding a basic, leucine-zipper protein that binds to these sites was isolated and designated Locus Control Region-Factor 1 (LCR-F1). This protein is a member of a new family of regulatory factors that contain a 63 amino acid 'CNC domain' overlapping the basic region. This domain is approximately 70% identical in the Drosophila Cap N Collar (CNC) protein, NF-E2 and LCR-F1. LCR-F1 transactivates an HS 2/gamma-globin reporter gene over 170-fold in transient transfection experiments specifically in erythroid cells. These results suggest that LCR-F1 may be a critical factor involved in LCR-mediated, human globin gene expression.